If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2s + -9)(8s + 1) = 0 Reorder the terms: (-9 + 2s)(8s + 1) = 0 Reorder the terms: (-9 + 2s)(1 + 8s) = 0 Multiply (-9 + 2s) * (1 + 8s) (-9(1 + 8s) + 2s * (1 + 8s)) = 0 ((1 * -9 + 8s * -9) + 2s * (1 + 8s)) = 0 ((-9 + -72s) + 2s * (1 + 8s)) = 0 (-9 + -72s + (1 * 2s + 8s * 2s)) = 0 (-9 + -72s + (2s + 16s2)) = 0 Combine like terms: -72s + 2s = -70s (-9 + -70s + 16s2) = 0 Solving -9 + -70s + 16s2 = 0 Solving for variable 's'. Factor a trinomial. (-1 + -8s)(9 + -2s) = 0Subproblem 1
Set the factor '(-1 + -8s)' equal to zero and attempt to solve: Simplifying -1 + -8s = 0 Solving -1 + -8s = 0 Move all terms containing s to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -8s = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -8s = 0 + 1 -8s = 0 + 1 Combine like terms: 0 + 1 = 1 -8s = 1 Divide each side by '-8'. s = -0.125 Simplifying s = -0.125Subproblem 2
Set the factor '(9 + -2s)' equal to zero and attempt to solve: Simplifying 9 + -2s = 0 Solving 9 + -2s = 0 Move all terms containing s to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2s = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2s = 0 + -9 -2s = 0 + -9 Combine like terms: 0 + -9 = -9 -2s = -9 Divide each side by '-2'. s = 4.5 Simplifying s = 4.5Solution
s = {-0.125, 4.5}
| 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 |